Participatory Approach in Project Management and Developement in Developing Countries - Awa, Awa Julius (European Journal of Multidisciplinary Studies, 2017)
Community development and management in most developing countries especially in Africa has been retarded because the main participants which are the local people have been left out or neglected in the implementation of developmental projects by either governments or some developmental agencies Whereas, participatory approach is a method of conceiving projects in which all the stake holders have a say in decision making which has greatly been the canker-worm of developing countries. They are various types of participatory approaches which may include Rapid Rural Appraisal (RRA), Participatory Rural Appraisal (PRA) and Participatory Assessment Monitoring and Evaluation (PAME) which could be analyzed as appropriate approach in realizing Community’s effort in developing countries and stresses the need for integration, participation and empowerment. With the application of these principles, the integration of various stake holders will enhances cross ‘sectoral’ harmonization of developmental objectives as well as increased coordination between agencies involved in the developmental process. Participation on its part gives the opportunity for consultation with those most directly affected which most at times are rural dwellers in developing countries; hence increasing the level of involvement of local people in the development process (Storey, 1999) and gives community members to take part in identifying priority areas, decision making and vulnerable groups to participate effectively in community development.
Keywords: Participation, Management, Project, Approach, Developing, Development, Community